Water treatment and artificial intelligence techniques: a systematic literature review research - Waidah Ismail; Nurzi Juana Mohd Zaizi; Naghmeh Niknejad; Mahadi Bahari; Rimuljo Hendradi; Mohd Zamani Zulkifli (Springer, 2024)
Indexed by WOS/Scopus/ERA